CONSTRUCTION AND VALIDATION OF AN EDUCATIONAL BOOKLET FOR THE PREVENTION OF FOOT INJURIES IN PEOPLE WITH DIABETES - Menezes, Beatrys Rosa Medeiros de; Souza, Laís dos Santos Rocha; Caetano, Laís Cristina de Oliveira; Souza, Maria Júlia Pereira de; Campos, Caroline Silva; Santos, Kelli Borges dos (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objectives: To construct and validate by agreement an educational booklet on the prevention of foot injuries in people with diabetes mellitus. Method: Methodological study was carried out from January 2020 to November 2022 and developed in two phases: construction of the booklet, and validation by agreement of the material by expert judges. A content validity coefficient of at least 0.80 was considered to ensure material validation. Results: In the first phase, among the 29 items evaluated in the booklet, two supported less than the determined, and then modifications were made to the material. In the second phase, all items showed agreement greater than 0.80. Conclusion: The booklet was validated from the point of view of offering assistance to professionals in the process of health education with patients with diabetes.